GPS Forelite: Inovasi Teknologi LoRa Berbasis AI dalam Meningkatkan Keselamatan Nelayan Kecil di Paciran, Lamongan - Akseptori, Ristanti; Praharsi, Yugowati; Amelia (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The safety of small-scale fishermen in Paciran District, Lamongan Regency, still faces serious challenges due to limited communication facilities and the absence of an early warning system. Small boats (<50 GT) used by fishermen at sea are highly vulnerable to high waves. In case of an emergency at sea, fishing boats are not equipped with technology that allows fishermen to request assistance from officers. This community service program aims to provide a solution through GPS Forelite, a LoRa and artificial intelligence (AI)-based vessel monitoring device equipped with a leak sensor, GPS, a two-way communication system, and an emergency button to improve the safety and efficiency of fishermen. The community service method was carried out through socialization, knowledge transfer, and training on the use of GPS Forelite. The socialization activity involved 32 fishermen and administrators of the Kandang Semangkon Fishermen's Association (Rukun Nelayan Kandang Semangkon) directly in a demonstration of the use of GPS Forelite to simulate leaks and use the emergency button. The results showed that 91% of the participants in the socialization and training gained a basic understanding of the importance of sailing safety aspects through the use of technology. The training participants successfully mastered the use of GPS Forelite, and the fishermen's groups as partners benefited from an increased sense of security and preparedness to face emergencies at sea. Another visible impact is the formation of collective awareness regarding occupational safety culture and the strengthening of the Nelayan Association (Rukun Nelayan) as a coordination center for technology implementation. Through this community service activity, a new approach has emerged that integrates technology transfer with active community participation, thus not only improving the safety of small-scale fishers but also building the capacity of fishing groups to become independent in adopting technological innovations.